Heart Rate Monitoring Robot by Using Arduino and NodeMCU ESP8266 - Jam, Mohamad Nur Aiman; Bakar, Lilywati; Abdul Wahab, Zurina (Progress in Engineering Application and Technology, 2022)
Nowadays, most electronic devices are wireless, and most industrial sectors also have already adopted industrial 4.0. This Arduino and NodeMCU ESP8266 Heart Rate Monitoring Robot helps to continually observe users remotely. People remain at home, avoid others, and change routine activities such as school and work in ways never imagined. The aim is to reduce direct human contact. This project will use a robot to automatically monitor the heart rate of patients at a hospital or clinic. The heart rate measuring code is written in Arduino IDE and uploaded to the Arduino UNO and NodeMCU ESP 8266 boards. The data will be transferred to the cloud for doctor monitoring.